Faktor Penentu Kepuasan Kerja Karyawan Outsourcing dan Pengaruhnya Terhadap Kinerja di Bank Rakyat Indonesia (BRI) Cabang Bangko - Masnun, Ariyanto (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2018)
This study aimed to analyze the analysis of the determinants of job satisfaction employee outsourcing at BRI Limited Liability Company Branch Bangkoand influence on the performance. This research usesjob satisfaction variablesand performanceto analyzefactors determinant of job satisfaction employee outsourcingat BRI Limited Liability Company Branch Bangko. Besides that, to analyze influence on the performance.The population in this study is all employee outsourcing at BRI Limited Liability Company BranchBangkofrom all divisions of the company. Both of which have a contractual term of less than one year or more than one year. This population is totaling 63 employeesinclude the following frontliner (Custumer service dan teller), PAU, IT, TKK, Secretary, payment point,driver, servant, and security. In this research uses survey methods namely with giving questionnaire to all of population is totaling 63 employees consists of employee outsourcing in all parts of the company. Data collectedusing questionnaire methodnamely with giving questionslist or questionnaire directly to respondents. Technical analysis of the data in this research uses factor analysis by program SPSS. The resulted of research showed that factor analysis found as main factor which influence satisfaction employee outsourcing at BRI limited liability company is work environment. The resulted of second hypothesis testing found that job satification unsignificant to satisfaction employee outsourcing at BRI limited liability company.